Cardiopulmonary phenotype associated with human PHD2 mutation - Talbot, N; Smith, T; Balanos, G; Dorrington, K; Maxwell, P; Robbins, P (Wiley, 2017)
Oxygen-dependent regulation of the erythropoietin gene is mediated by the hypoxiainducible factor (HIF) family of transcription factors. When oxygen is plentiful, HIF undergoes hydroxylation by a family of oxygen-dependent prolyl hydroxylase domain (PHD) proteins, promoting its association with the von Hippel-Lindau (VHL) ubiquitin E3 ligase and subsequent proteosomal degradation. When oxygen is scare, the PHD enzymes are inactivated, leading to HIF accumulation and upregulation not only of erythropoietin expression, but also the expression of hundreds of other genes, including those coordinating cardiovascular and ventilatory adaptation to hypoxia. Nevertheless, despite the identification of over 50 mutations in the PHD-HIF-VHL pathway in patients with previously unexplained congenital erythrocytosis, there are very few reports of associated cardiopulmonary abnormalities. We now report exaggerated pulmonary vascular and ventilatory responses to acute hypoxia in a 35-year-old man with erythrocytosis secondary to heterozygous mutation in PHD2, the most abundant of the PHD isoforms. We compare this phenotype with that reported in patients with the archetypal disorder of cellular oxygen sensing, Chuvash polycythaemia, and discuss the possible clinical implications of our findings, particularly in the light of the emerging role for small molecule PHD inhibitors in clinical practice.